Non‐medical use of benzodiazepines and GABA analogues in Europe. Issue 4 (15th September 2020) - Hockenhull, Joanna; Amioka, Elise; Black, Joshua C.; Forber, Alyssa; Haynes, Colleen M.; Wood, David M.; Dart, Richard C.; Dargan, Paul I.
Abstract : Aims: We investigated the prevalence of non‐medical use (NMU) of benzodiazepines and GABA analogues in Europe. Methods: Data were collected using the online Non‐Medical Use of Prescription Drugs (NMURx) survey from France, Germany, Italy, Spain and the UK. Results: The study included 55 223 eligible surveys which, after post‐stratification weights were applied, represented approximately 260 million European adults. Lifetime NMU of benzodiazepines was highest in Spain (6.5%, 95% CI: 6.0–7.0) and lowest in Germany (1.7%, 1.5–2.0). Lifetime NMU of GABA analogues was highest in Germany (5.4%, 5.0–5.7) and lowest in France (2.2%, 1.9–2.5) and the UK (2.2%, 1.9–2.6) While no notable difference was observed for France or the UK, there was a higher prevalence of last 12‐month NMU of benzodiazepines compared to GABA analogues in Italy (2.4 times higher) and Spain (3.0 times higher) and a higher prevalence of NMU of GABA analogues compared to benzodiazepines in Germany (2.6 times higher). Conclusion: This study shows that there is variation in NMU of benzodiazepines and GABA analogues among countries. Of particular interest is the high incidence of GABA analogue NMU in Germany and benzodiazepine NMU in Spain. Further research to identify factors and motivations responsible for the higher prevalence observed are essential to inform public health policies in those countries.